Impact of water ion content on milk protein concentrate gel properties - Xu, Yanbing; Zhou, Xilong; Diao, Junhui; Zhang, Juan; Liu, Zhenmin (Frontiers in Nutrition, 2026)
This study investigated how differences in trace ions present in food industrial and household water affect the formation and properties of milk protein concentrate (MPC) gels. MPC dispersions were prepared using reverse osmosis (RO) water and boiled tap water, a type of water commonly used for daily household consumption, while dispersions prepared with ultrapure water served as the control. The regulatory role of trace ions was systematically characterized by analyzing the ionic composition of the water, the conductivity and zeta potential of the MPC dispersions, the microstructure, water holding capacity, and rheological properties of the MPC gels. The results show that even modest ion content (1.4 mmol/L) in boiled tap water can significantly alter MPC gel properties. Although gels prepared with boiled tap water exhibited a denser microstructure, their elastic modulus and water holding capacity were lower than those of gels prepared with RO water. These outcomes are attributed to the higher concentrations of divalent cations (Ca2+ and Mg2+) in boiled tap water, which induced pre-aggregation through electrostatic screening and salt-bridge formation, ultimately leading to insufficient cross-linking between aggregates. Nonetheless, due to the low ion content in RO water and boiled tap water, the resulting gels showed no differences in appearance and rheological behavior under large deformation.